Whistle sound detection and behaviour of male dolphin bottle nose (Tursiops aduncus) using noisy time domain modelling in captivity - Muhammad Zainuddin Lubis; Mahendra Kumar; Kasih Anggraini (Aceh Journal of Animal Science, 2017)
Whistle sound is a voice that is intended to echolocation, whistle sound is a major role in internal and inter-group communication. The objective research is to know the power spectral patterns and fluctuations in sound based on frequency of the sounds produced by dolphins and observing the position of dolphins. Noisy Time Domain (NTD) and behaviour using the underwater camera, and also comparing between time and sound spectrum. Data recording was taken at the Safari Park of Cisarua Bogor in Indonesia, by taking data in show pool. The results showed that salinity before feeding time in the show pool with replication 1,2, and 3 has salinity value that is equal to 30 ‰. Data at the show pool before feeding with replications 1,2, and 3 has a salinity of 29 ‰. Sound whistle 3 before feeding time of 28.03 dB with the frequency interval of 14 642 Hz-16000 Hz. F-test at the show pool before meals has heterogeneous value. Treat before meals at the show pool has a value of P 0.001 and P 0.001. Value Noisy Time Domain have differences with each other and have a lot of different sound patterns. In general, there are real differences are evidenced by F test on a range of time at each whistle on show pool in the time before meals. In general, there is a noticeable difference in the range of time at each whistle on show pool in the time before meals. The behaviour of dolphins have a habit that has the movement toward the surface of the pool and movement and position will be influenced frequency and intensity value.